AN EXPERIMENTAL INVESTIGATION OF THE OPTIMUM REPLACEMENT RATIO OF COARSE GRAVEL WITH EXPANDED POLYSTYRENE BEADS IN CONCRETE - SALIH, ANMAR H.; HUSSAIN, HUSSAIN DHAFIR; Abu Altemen, Ahmed Abbas G.; Jameel, Nibras Z (Journal of Applied Engineering Science, 2023)
Previous researches have shown that partial replacement of aggregates with Expanded Polystyrene (EPS) in concrete mixes reduces both the density and compressive strength of concrete, but enhances its durability. As there is no effort was made to determine the optimum EPS/gravel replacement ratio in a concrete mixture, this study triedl to determine this ratio. An experimental investigation is performed by using six different concrete mixes produced by partially replacing gravel with an equivalent volume of EPS beads. The adopted volumetric replacement ratios of coarse aggregate by EPS were (11%, 22%, 33%, 44%, and 55%). The results indicated that A drop in the density of both the fresh and hardened concrete was found to be in the range (of 0% to 35%) compared to the corresponding density value of the base mix (without EPS). Concrete compressive strength was also found to drop in the range (0% to 91%) compared with the corresponding value of the base mix. Within the limit of this work, it was found that the 22% replacement volumetric ratio of coarse aggregate with EPS is the optimum ratio based on a ratio of the drop in density to the drop in compressive strength. Generally, it was concluded that the optimum volumetric replacement ratio lies between 15% to 30%, according to the comparison with other prior studies.
Keywords: expanded polystyrene (EPS), lightweight concrete, optimum replacement ratio, compressive strength